A JOURNEY OF AN ADOLESCENCE IN 3DS (DECENCY TO DEVIANCY TO DELINQUENCY/ CHILD IN CONFLICT WITH LAW) - Dubey, Divya; Kewalramani, Soni; Sanyal, Shubhra (International Journal of Psychosocial Rehabilitation, 2020)
Adolescence, is considered as a transitional phase of growth and development between childhood and Adulthood. The World Health Organisation (WHO) defined an adolescent as any person between ages 10 and• This is the age where number of Physical, Emotional, Intellectual and Psychological changes take place. It is a sensitive and crime prone age, where everything in and around the adolescence is changing so rapidly, from their Psychological changes to Physical to Emotional changes, where brain development still taking place, the risks taken and mistakes made by young offenders may be more outside of their control than we think, said Steinberg.• Stanley Hall, the first president of the American Psychological Association, described this stage as “Storm and Stress” refers to the period of adolescence in which teenagers are in conflict with their parents, are moody and engage in risky behavior.